Understanding the impact of DNMT3A Knockout on K562 cell sensitivity towards epigenetic drug treatments - Mah, Lian-Khye (2019)
DNMT3A mutation has been seen as a marker of acute myeloid leukaemia. DNMT3A mutation can cause genome methylation changes and the reliance on other epigenetic modifiers including other methyltransferases for maintaining regular gene expression for survival. The loss of the remaining epigenetic modifiers may cause further epigenetic destabilisation that is incompatible with viability. Therefore this study proposes that the altered epigenetic landscape of DNMT3A knockout cells can be exploited for regulating cell proliferation by exposing the cells to epigenetic drugs. This study utilises a 13bp deletion in exon 7 of the DNMT3A gene to represent mutated DNMT3A function. The cells were then exposed to epigenetic drugs such as Azacitidine, JQ1, and GSK343 that are able to inhibit epigenetic modifiers including methyltransferases. The IC50 was calculated from cell viability values using CellTiter-Glo cell viability assay to determine drug sensitivity. The data derived showed that DNMT3A knockout and Control cells portrayed similar sensitivities towards epigenetic drugs. This shows that the changes in methylation state from the loss of DNMT3A function may not have a significant impact on drug sensitivity. Future studies including the use of other therapeutic mechanisms should be conducted to understand the extent of drug sensitivities in DNMT3A mutant cells.